2009
DOI: 10.1158/0008-5472.can-09-2131
|View full text |Cite
|
Sign up to set email alerts
|

ATAD2 Is a Novel Cofactor for MYC, Overexpressed and Amplified in Aggressive Tumors

Abstract: The E2F and MYC transcription factors are critical regulators of cell proliferation and contribute to the development of human cancers. Here, we report on the identification of a novel E2F target gene, ATAD2, the predicted protein product of which contains both a bromodomain and an ATPase domain. The pRB-E2F pathway regulates ATAD2 expression, which is limiting for the entry into the S phase of the cell cycle. We show that ATAD2 binds the MYC oncogene and stimulates its transcriptional activity. ATAD2 maps to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
260
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 209 publications
(276 citation statements)
references
References 39 publications
12
260
1
Order By: Relevance
“…Interestingly, Atad2-L was strictly associated with the nuclear non-soluble fraction, suggesting its tight association with chromatin and/or nuclear matrix ( Figure 3a, lanes 2 and 4). This is in agreement with the data of (Ciro et al, 2009), who observed the association of human ATAD2, which corresponds to Adat2-L, with the nuclear matrix. In contrast, the short form was essentially present in the soluble fraction ( Figure 3a, lane 3).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Interestingly, Atad2-L was strictly associated with the nuclear non-soluble fraction, suggesting its tight association with chromatin and/or nuclear matrix ( Figure 3a, lanes 2 and 4). This is in agreement with the data of (Ciro et al, 2009), who observed the association of human ATAD2, which corresponds to Adat2-L, with the nuclear matrix. In contrast, the short form was essentially present in the soluble fraction ( Figure 3a, lane 3).…”
Section: Resultssupporting
confidence: 93%
“…Here, we identified ATAD2 as one of these genes and showed its overexpression, compared with normal somatic tissues, in a strikingly large number of unrelated somatic cancers. These data confirm and extend the observation of Ciro et al (2009), who had detected a frequent overexpression of ATAD2 in seven different cancer types. In addition, detailed clinical information on a cohort of lung and breast cancer patients allowed us to evidence Figure 6 The ATAD2 knock-down induces global transcription changes associated with increased histone dynamics.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations